The Effectiveness of Small-Sided Game Practice on Improving Basic Futsal Skills - Khurrohman, Moch Fath; Purwanto, Sugeng; Nopembri, Soni; Festiawan, Rifqi (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
The purpose of this study was to empirically determine the provision of small-sided games 4vs2, 4vs3, and 4vs4 exercises on the basic skills of futsal athletes. This research is included in the experimental research. Participants of the study were 30 male teenage futsal athletes in Banyumas Regency. The data retrieval technique of this study used passing-controlling tests. The analysis used the normality test, homogeneity test, paired t-test test, and independent t-test with a significance level of 0.05. This study showed that the administration of SSG 4v2, 4v3, 4v4 exercises significantly influenced the fundamental skill improvement of futsal athletes. The largest increase was achieved by providing the SSG 4vs4 group with an average of Â± 13.63. The results of the one-way Anova test showed that there were differences among 4vs2, 4vs3, and 4vs4 exercises. The increase might be because the SSG 4vs4 exercise suits the actual futsal game. Thus it encourages athletes to perform as many passing movements as possible. Therefore, SSG 4vs4 training is more effective in improving the basic skills of futsal athletes. It is crucial for practitioners because it allows the provision of exercises simultaneously so that training stimulus becomes more efficient.